EFFECT OF CAPITAL STRUCTURE, PROFITABILITY, DIVIDEND POLICY, COMPANY SIZE ON PROPERTY & REAL ESTATE COMPANY VALUE - Roslinda Febri Yani; Tanti Widyaningsih; Audrio Yapardi (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
Background  The property & real estate company until now has made progress, with the level of development and is still being worked on today.This study aims to test the effect of capital structure, profitability, dividend policy and firm size on firm value. The study was conducted on Property & Real Estate Companies during the 2018-2020 period listed on the IDX with a total population of 61 companies, in this study using the Purposive Sampling method. Thus, the sample found by the researcher was 36 companies. This study uses secondary data, which means that the source of the data given to the data collector is indirectly in the form of a document taken from the company's financial statement data and then used as a sample which has been published on the website www.idx.co.id. Method The researcher used descriptive analysis method and multiple linear regression analysis method. In this study, firm value is the dependent variable. Meanwhile, Capital Structure, Profitability, Dividend Policy and Company Size are independent variables. Result In this study, the researchers showed that the test results simultaneously in all independent variables have an influence on firm value. Conclution However, the results of the test conducted by the researcher partially independent variable, namely company size has a negative effect on company value and other independent variables have no effect on company value.